UNFCCC Agricultural Greenhouse Gas Database 2021 - Dittmer, Kyle M.; Wollenberg, Eva Karoline; Cohen, Milo; Egler, Cecelia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This database was compiled using each Party's most recent National Communication (NC), Biennial Update Report (BUR), or Common Reporting Format (CRF) table submitted to the United Nations Framework Convention on Climate Change (UNFCCC). To assure relative consistency in our data extraction and calculations, we compared our results to UNFCCC Greenhouse Gas Profiles when available or relevant. We sought to compile gross and net national emissions, national agricultural emissions (methane and nitrous oxide emissions only; no CO2 emissions/removals from the Agricultural sector), and national AFOLU/LULUCF emissions. To view the formula to calculate each field above, see the sheets "Non-Annex I Inventory" and "Annex I Inventory." All values are reported in gigagrams (Gg) or metric tonne for emissions per capita. For Parties that reported emissions via LULUCF format, we summed net land-use emissions with agricultural non-CO2 emissions to report emissions via AFOLU formatting. We calculated carbon dioxide equivalent (CO2e) in accordance with global warming potentials (GWP) recommend in the IPCC Fifth Assessment Report (CH4 = 28; N2O = 265) for Parties that reported gasses individually and provided the GWP used to calculate CO2e in the inventory (if the Party reported emissions in CO2e). For Parties that only reported emissions in CO2e without identifying the GWP used or did not report individual GHG emissions, we extracted the CO2e value identified in the report. To better understand the Party’s GHG reporting format, we also recorded which IPCC Guidelines for National GHG Inventories was used (IPCC 1996, 2006). Common reporting format (CRF) tables were used for all data extraction from Annex I Parties. To calculate emissions based on alternative GWPs for each Party, input the GWP values of interest into cells T2 (methane) and T3 (nitrous oxide) within the sheets "Non-Annex I Inventory" and "Annex I Inventory."